The Effectiveness Of Fingerprint Implementation In Improving Student Discipline At State Vocational High School 01 In Bengkulu City - Dewi Mariska Handayani; Harius Eko Saputra; Yusuarsono Yusuarsono; Bando Amin C. Kader (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effectiveness of implementing the Fingerprint system in improving student discipline at the State Vocational High School 01 (SMKN 01) Bengkulu City. This research uses a qualitative method presented descriptively. The research informants consisted of 5 individuals, including 2 key informants and 3 main informants. Data collection techniques included interviews, documentation, and observation. The data analysis techniques used in this study were data collection, data reduction, data presentation, and conclusion drawing and verification. Based on the research findings and discussion using the effectiveness measurement theory by Duncan (in Richard M. Steers, 1984:53), three indicators were applied. The results indicate that the effectiveness of the Fingerprint implementation in improving student discipline at SMKN 01 Bengkulu City can be concluded as follows: 1) Goal Achievement: This is reflected in the gradually improving level of student discipline. 2) Integration: SMKN 01 Bengkulu City conducted socialization regarding the Fingerprint attendance system and recorded students’ fingerprints and facial data from class to class for two weeks prior to its full implementation. 3) Adaptation: The school created schedules for students to help them become accustomed to their responsibilities and disciplined in arriving earlier.